BIAYA MUTU (QUALITY COST) DI LEMBAGA PENDIDIKAN ISLAM: QUALITY COST - Nafi'; Asrowi Ardi Sulistyo; Revita Galuh Maharani (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang OKU Timur Sumatera Selatan, 2026)
Quality cost is a crucial component of modern management, aiming to ensure quality improvement through effective and efficient cost management. This concept was initially applied to the industrial sector but was later adapted by service providers, including Islamic educational institutions. This article aims to analyze the application of quality cost in Islamic educational institutions and identify the challenges that arise in its implementation. The study employed a library research method by reviewing various sources, such as books, journal articles, and research findings from the last five years related to quality cost management and Islamic education financing. The study results indicate that quality cost is divided into four main categories: prevention costs, appraisal costs, internal failure costs, and external failure costs. The implementation of these four categories is crucial for reducing budget waste, increasing the effectiveness of educational services, and strengthening the institution's quality assurance system. However, the implementation of quality cost in Islamic educational institutions still faces various obstacles, such as budget constraints, low quality literacy, weak administrative documentation, resistance to change, and a suboptimal Internal Quality Assurance System (SPMI). These findings emphasize the need to strengthen management capacity, modernize administrative systems, and improve institutional commitment to managing quality costs sustainably